Design, biological evaluation, and molecular modelling insights of cupressic acid derivatives as promising anti-inflammatory agents. (31st December 2023) - Soliman, Amal F.; Elimam, Diaaeldin M.; El-Senduny, Fardous F.; Alossaimi, Manal A.; Alamri, Mubarak; Abdel Bar, Fatma M.
Abstract: The major labdanes in the oleogum resin of Araucaria heterophylla (Salisb.) Franco, 13-epi-cupressic acid (1 ) and acetyl-13-epi-cupressic acid (2 ) were used to prepare seven new (3 –9 ), along with one known (10 ) derivatives. RAW264.7 cells were used to evaluate the anti-inflammatory activity of the derivatives (1 –10 ) via measuring the level of COX-2 expression and IL-6. Pre-treated RAW264.7 cells with 1 –10 (except for derivative 7 ) at 25 µM for 24h exhibited downregulation of COX-2 expression in response to LPS stimulation. Moreover, pre-treatment with compounds 1, 2, or 3 significantly attenuated the LPS-stimulated IL-6 level in RAW264.7 cells ( p < 0.05). A docking study was conducted against phospholipase A2 (PLA2), a crucial enzyme in initiating the inflammatory cascade. The significant structural features of compounds (1 –10 ) as PLA2 inhibitors included the carbonyl group at C-4 (free or substituted) and the hydrophobic diterpenoid skeleton. This study suggested 13-epi-cupressic acid as a scaffold for new anti-inflammatory agents.